2007
DOI: 10.1002/nau.20326
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of urgency: regional difference of vanilloid receptor expression in the human urinary bladder

Abstract: The symptoms of SU were associated with the increased expression of TRPV1 mRNA in the trigonal mucosa. No upregulation or regional differences of TRPV1 mRNA were seen in IDO patients. TRPV1 may play a role in SU and premature first bladder sensation on filling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 33 publications
1
51
0
Order By: Relevance
“…A trend suggesting a similar correlation was found with TRPV1 immunoreactive fibers. Very recently, Liu et al 43 demonstrated that in patients with sensory urgency without DO, TRPV1 mRNA is increased in the trigonal mucosa and correlates with a lower volume associated with first bladder sensation to urinate. Thus, the possibility of inactivating bladder C-fibers by the two neurotoxins seems to be an attractive possibility to treat urgency refractory to antimuscarinic drugs.…”
Section: Results With Rtx and Btx-a In Patients With Urgencymentioning
confidence: 99%
“…A trend suggesting a similar correlation was found with TRPV1 immunoreactive fibers. Very recently, Liu et al 43 demonstrated that in patients with sensory urgency without DO, TRPV1 mRNA is increased in the trigonal mucosa and correlates with a lower volume associated with first bladder sensation to urinate. Thus, the possibility of inactivating bladder C-fibers by the two neurotoxins seems to be an attractive possibility to treat urgency refractory to antimuscarinic drugs.…”
Section: Results With Rtx and Btx-a In Patients With Urgencymentioning
confidence: 99%
“…Urothelial TRPV1 expression and sensitivity were increased in patients with IDO (45). In women with sensory urgency, TRPV1 mRNA expressed in trigonal mucosa was not only increased, but also inversely correlated with the bladder volume at first sensation of filling during cystometry, further indicating that TRPV1 plays a role in premature bladder sensation (191).…”
Section: Capsaicin and Rtxmentioning
confidence: 88%
“…Urothelial cells release ATP, NO, or ACh, transmitters that can act on afferent neurons to alter their excitability (6,10,26,30,34,35,44,54). Thus alterations in TRP channel expression or function, which have been reported in pathological conditions (1,2,12,22,37), might lead to altered extracellular levels of neurotransmitters in bladder mucosa and in turn to altered afferent nerve activity and altered bladder function. Indeed, previous studies reported upregulation of ATP release from bladders that are overactive as a result of inflammation (47) or spinal cord injury (45) and increased ATP release from urothelial cells from human patients (51) or cats (11) with interstitial cystitis (for a review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of TRP channels in the urothelium, several studies using intravesical administration of selective agonists (9,23,28,40,50,58), genetically engineered mice lacking specific TRP channels (TRP Ϫ/Ϫ mice) (13,14,28), or investigating the changes in the expression of TRP channels in various pathological conditions (1,22,37) have attempted to establish a role of these channels in bladder function. Intravesical administration of a TRPV1 agonist (capsaicin) (58), TRPA1 agonists (trans-cinnamaldehyde or allyl isothiocyanate) (50), and a TRPM8/TRPA1 agonist (menthol) (40), have excitatory effects on the reflex bladder activity, increasing micturition frequency, and reducing voided volume.…”
mentioning
confidence: 99%